(untitled) (Eduscotech, 2024)
This study investigates the effectiveness of using descriptive dialogues combined with information gap activities to enhance the speaking skills of first-grade students at SMK Maospati Magetan. Employing a descriptive qualitative research design, the study examines how these instructional techniques improve students’ oral fluency, classroom engagement, and communicative competence. Data were collected through classroom observations, students’ speaking performances, instructional documents, and interviews with the English teacher. The analysis focuses on identifying improvement patterns, learning challenges, and the pedagogical implications of implementing the techniques. The findings show that descriptive dialogues, when integrated with information gap activities, significantly increase students’ participation, confidence, and willingness to speak. Improvements were observed in pronunciation, vocabulary use, sentence construction, and fluency. The requirement to exchange missing information fostered authentic communication and meaningful peer interactions. However, challenges such as limited vocabulary, low self-confidence, and difficulty maintaining conversational flow remained evident. These constraints were influenced by varying levels of language exposure and learners’ differing abilities to process information during speaking tasks. The study concludes that combining descriptive dialogues and information gap activities is an effective instructional strategy for teaching speaking, aligning with communicative language teaching principles by promoting learner-centered, interactive, and purpose-driven communication. Recommendations include integrating structured dialogue practices, providing vocabulary scaffolding, offering continuous feedback, and using contextualized materials to sustain motivation and participation.